A Compact Quad-band CPW-fed Planar Resonator for Multiple Wireless Communication Applications - Aamir Khan; Syeda I. Naqvi; Farzana Arshad; Yasar Amin; Hannu Tenhunen, (Applied Computational Electromagnetics Society Journal (ACES), 2021)
This article presents a low-cost, compact antenna with coplanar waveguide (CPW) feed line for multiband wireless applications. The presented multiband radiator is envisioned for integration into microwave circuits and portable RF devices. The prototype is realized on 1.6 mm thick readily available FR4 substrate with a compact geometrical size of 24×32 mm2. The acquired quad-bands are centered at: 2.45, 3.5, 5.2 and 5.8 GHz justifying the appropriateness of the proposed radiator for the WLAN and WiMAX applications, as well as Bluetooth and ISM wireless standards. From the aspect of integration into transportable handheld devices and system designing, the presented compact antenna illustrates more expandability and flexibility. The radiation characteristics measured in the E and H-planes for desired operating frequencies are monopole-like and omni-directional, respectively. A sufficient gain is also achieved. Simulated as well as experimental results exhibit agreeable behavior.